Urolithiasis in Songklanagarind Hospital; southern Thailand - M Marikatat; A Apiwatgaroon; C Pripatnanont (Journal of Health Science and Medical Research (JHSMR), 2002)
Objective: To address the epidemiology of urolithiasis in Songklanagarind Hospital; southern Thailand. Materials and Methods: Over the four-year period, 1997 - 2000, 5,445 urolithiasis patients searching for treatment in Songklanagarind Hospital were enrolled, and the following data recorded; age, sex, occupation, domicile, diagnosis and procedure of treatment. For stone composition study, calculi from 807 patients collected from operating theater and ESWL (Extracorporeal Shock Wave Lithotripsy) Unit of Songklanagarind Hospital were analysed using infrared spectroscopy. Results: On average, 1,362 urolithiasis patients per year searched for treatment at Songklanagarind Hospital, with a male to female ratio of 1.6 : 1 and common age group of 41-50 years. Thirty four percent of the patients were farmers. 58.7% were diagnosed as renal calculi, 35.8% ureteric calculi and 5.5% vesical or urethral calculi. Ninety percent of renal calculi were treated with ESWL and 10% by surgery, while ureteric calculi were treated by endoscopic surgery (56%), ESWL (35%) and surgery (9%). Vesical calculi were treated by endoscopic surgery (93%) and surgery (7%). In 55.5% of males and 57.5% of females with upper urinary tract (UUT) calculi, the calculi were composed of one component, of which oxalate was the most common, whereas 71.6% of males and 64.3% of females with lower urinary tract (LUT) calculi had pure stone with uric acid being the most common component. Among mixed stones of upper tract and lower tract calculi, the most common components were oxalate and phosphate. Conclusion: Approximately 1,350 patients are treated for urolithiasis each year at Songklanagarind Hospital. The most common component for pure stones of the upper tract calculi is oxalate, whereas that of lower tract calculi is uric acid. Common components for mixed stone of upper tract and lower tract calculi are oxalate and phosphate.